Small Farms and Food Supply in Russian Border Regions: Regional Patterns and Differences - Voloshenko , Ksenya Yu.; Ivanova, Olga P.; Lialina, Anna V.; Morachevskaya, Kira A.; Plotnikova, Angelina P. (Economy of Regions, 2026)
In the context of sanctions imposed by countries deemed “unfriendly” by the Russian government, issues of security, particularly food security, have become especially significant for border regions due to their geostrategic importance. At the same time, ongoing trends toward the consolidation of agricultural production and its spatial concentration in agglomeration zones highlight the role of small farms. These farms are essential for preserving agricultural diversity and supporting the sustainability of rural areas. This article examines regional differences in the contribution of small farms to food production capacity of Russian border regions. Using an original spatial typology based on levels of food production capacity and the share of small farms, 48 border regions (within Russia’s borders as of 2022) were classified into four types across key product groups: milk, livestock and poultry, vegetables, and fruit. The results show that established agricultural specialization, which is largely determined by agroclimatic conditions, remains a key factor in regional differentiation. Additional geographic characteristics, including region size, distance from major population centres, transport accessibility, degree of peripherality, and settlement dynamics, also play an important role, as do the regime and functions of state borders. The contribution of small farms to the production of certain goods remains relatively stable, particularly in border contact zones. However, institutional factors, especially state support policies aimed at import substitution, have had mixed effects. In some cases, such support has strengthened small farms, while in others it has reduced their relative importance due to the rapid expansion of large agricultural enterprises. The findings can inform the development of targeted state support measures for small farms. Future research should focus on improving their spatial organization to enhance food security in border regions.